2019
DOI: 10.1002/pon.5126
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control trial of stress management for caregivers of stem cell transplant patients: Effect on patient quality of life and caregiver distress

Abstract: Background Psychological interventions reduce caregiver distress (CG‐distress). Less distress in caregivers may contribute to improved patient quality of life (QoL), but empirical evidence is lacking. Will a caregiver stress management intervention improve patient QoL? Methods In this replication study, we randomized 155 allogeneic hematopoietic stem cell transplant (Allo‐HSCT) patients and caregivers to PsychoEducation, Paced Respiration, and Relaxation (PEPRR) or enhanced treatment as usual (eTAU). We provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…Although prior caregiver interventions have shown reductions in stress and psychological distress among caregivers of HCT recipients, no studies have demonstrated improvements in caregiver-reported QOL or caregiving burden. [16][17][18] Improvements in both QOL and caregiving burden are notable because of the intense care demands of HCT recipients, the chronic nature of caregiving in this population, and the critical need to address caregiving burden as a major contributor to caregivers' moral exhaustion and morbidity. [12][13][14][15] Cancer April 15, 2020 We also have demonstrated the preliminary efficacy of BMT-CARE for improving anxiety and depression symptoms as well as caregivers' self-efficacy and coping skills with medium to large effect sizes.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Although prior caregiver interventions have shown reductions in stress and psychological distress among caregivers of HCT recipients, no studies have demonstrated improvements in caregiver-reported QOL or caregiving burden. [16][17][18] Improvements in both QOL and caregiving burden are notable because of the intense care demands of HCT recipients, the chronic nature of caregiving in this population, and the critical need to address caregiving burden as a major contributor to caregivers' moral exhaustion and morbidity. [12][13][14][15] Cancer April 15, 2020 We also have demonstrated the preliminary efficacy of BMT-CARE for improving anxiety and depression symptoms as well as caregivers' self-efficacy and coping skills with medium to large effect sizes.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the prolonged caregiving process required for HCT, BMT‐CARE led to improvements in both QOL and caregiving burden with medium effect sizes. Although prior caregiver interventions have shown reductions in stress and psychological distress among caregivers of HCT recipients, no studies have demonstrated improvements in caregiver‐reported QOL or caregiving burden . Improvements in both QOL and caregiving burden are notable because of the intense care demands of HCT recipients, the chronic nature of caregiving in this population, and the critical need to address caregiving burden as a major contributor to caregivers' moral exhaustion and morbidity …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations